2022
DOI: 10.3389/fmolb.2022.1032517
|View full text |Cite
|
Sign up to set email alerts
|

A cutting-edge immunomodulatory interlinkage between HOTAIR and MALAT1 in tumor-associated macrophages in breast cancer: A personalized immunotherapeutic approach

Abstract: Breast cancer (BC) is one of the most common cancers, accounting for 2.3 million cases worldwide. BC can be molecularly subclassified into luminal A, luminal B HER2-, luminal B HER2+, HER2+, and triple-negative breast cancer (TNBC). These molecular subtypes differ in their prognosis and treatment strategies; thus, understanding the tumor microenvironment (TME) of BC could lead to new potential treatment strategies. The TME hosts a population of cells that act as antitumorigenic such as tumor-associated eosinop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…In these TAMs, the MALAT1 and HOTAIR silencing promotes the upregulation of CD80 and MSLN and the downregulation of VEGF-A. Furthermore, this study showed a cytotoxicity decrease in CD8 + T cells against TNBC cells treated with anti-PD-L1 inhibitor and cultured under conditioned media derived from TAMs with MALAT1 and HOTAIR silencing, indicating the role of both lncRNAs as tumor-extrinsic negative modulators of the antitumoral immune response in BC ( 109 ) ( Figure 3 ).…”
Section: Lncrnas As Tumor-extrinsic Regulators Of the Time In Bcmentioning
confidence: 71%
“…In these TAMs, the MALAT1 and HOTAIR silencing promotes the upregulation of CD80 and MSLN and the downregulation of VEGF-A. Furthermore, this study showed a cytotoxicity decrease in CD8 + T cells against TNBC cells treated with anti-PD-L1 inhibitor and cultured under conditioned media derived from TAMs with MALAT1 and HOTAIR silencing, indicating the role of both lncRNAs as tumor-extrinsic negative modulators of the antitumoral immune response in BC ( 109 ) ( Figure 3 ).…”
Section: Lncrnas As Tumor-extrinsic Regulators Of the Time In Bcmentioning
confidence: 71%
“…At the beginning of oncogenesis, TAMs take on an M1-like pro-inflammatory phenotype, triggering an immune response that prevents tumor development. In a recent research investigation, T. Amer and colleagues sought to epigenetically control two immune-modulating proteins, CD80 and mesothelin (MSLN), which are highly expressed in breast cancer and have pro-tumorigenic impacts [ 208 ], in order to modulate the anti-inflammatory properties of TAMs in various breast cancer subtypes (hormonal, HER2+, and TNBC). They concentrated on MALAT-1 and HOTAIR as two particular lncRNAs to comprehend their regulatory functions in regulating the tumorigenic activity of TAMs.…”
Section: Reproductive Cancersmentioning
confidence: 99%
“…They concentrated on MALAT-1 and HOTAIR as two particular lncRNAs to comprehend their regulatory functions in regulating the tumorigenic activity of TAMs. The researchers investigated the influence of altering MALAT-1 and HOTAIR on the expression of CD80 and MSLN in BC TAMs [ 208 ]. Increased expression of CD80 and MSLN was accompanied by downregulation of MALAT-1 and HOTAIR, indicating that these lncRNAs may have cell-specific functions in TAMs [ 208 ].…”
Section: Reproductive Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…HOTAIR has been reported to be an upstream regulator of MALAT1, and promising results have been obtained from the use of MALAT1 and HOTAIR in regulating oncogenic immune-modulatory proteins CD80 and MSLN in tumor-associated macrophages (TAMs) [ 120 ]. This study also investigated the association between HOTAIR and MALAT1 as regulators, highlighting the regulatory role of MALAT1 and HOTAIR lncRNAs in controlling the tumorigenic activity of TAMs in BC and examining the impact of manipulating MALAT1 and HOTAIR on the expression of CD80 and MSLN in TAMs for HER2 + and TNBC BC.…”
Section: The Role Of Hotair In Breast Cancer Managementmentioning
confidence: 99%